WAITING TIMES HEALTH POLICY IN POLAND - Wolan, Maja; Jacek, Anna; Gugała, Barbara (Review of European and Comparative Law, 2017)
In Poland, a provisions of the Act of 27 August 2004 on health care services financed from public funds1 defines the principles of the waiting list . Waiting list is one of the way to ensure equal access to health care services . Running waiting lists for health care services is the statutory duty of all providers and considers only first-time patients . The Act of 27 August specifies the responsibilities of the provider in relation to the patient, and to managing the waiting lists . Provider is obliged to give the patient information on the scope of health care services, the waiting time for health services, and information regarding the confirmation of the right to health care benefits at the first visit of the patient . In addition, a patient at the point of registration should receive comprehensive information on clinics . Minister of Health in regulation of 26 September 2005 on medical criteria, described what criteria should be guided by the provider entering a beneficiary on waiting lists for health care services . In case of deterioration of patients’ health, which may indicate the need to provide earlier health care service, the patient is obliged to inform the provider . Then, for medical reasons, the time of providing the health care service should be adjusted . Health care provider has no right to refuse to register patient on the waiting list to obtain health care servic. National Health Fund web sites provide information on waiting lists main-tained by individual providers, the number of people, by urgent cases and cases of a stable, and the average waiting time for providing medical services and infor-mation about other healthcare providers who offer benefits in within a shorter period of time